Structural analysis of Edwardsiella tarda PCM 1155 O-polysaccharide revealed the presence of unique β-L-RhapNAc3NAc derivative. (November 2021) - Kaszowska, Marta; Górska, Sabina; Knirel, Yuriy; Kalinchuk, Nadezhda; Gamian, Andrzej; Katzenellenbogen, Ewa
Abstract: The chemical structure of the lipopolysaccharide O-polysaccharide repeating unit of Edwardsiella tarda strain PCM 1155 was studied for the first time. The complete structure of repeating unit was investigated by chemical methods, 1 H and 13 C nuclear magnetic resonance (NMR) spectroscopy, and matrix-assisted laser-desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). The rarely occurring monosaccharide, 2, 3-diacetamido-2, 3, 6-trideoxy-l -mannose (L-Rha p NAc3NAc) was identified. The following structure was established: Image 2 Graphical abstract: Image 1 Highlights: Infection caused by Edwardsiella tarda leads to huge economic losses in fish aquaculture. The novel O-specific polysaccharide structure of E. tarda 1155 has been established. The OPS was found to contain rarely occurring 2, 3-diacetamido-2, 3, 6-trideoxy-l -mannose residue.